2021
DOI: 10.3390/vibration4020025
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Effects of Drill Operator Posture on Vibration Exposure and Temporary Threshold Shift of Vibrotactile Perception Threshold

Abstract: The present study involved performing an experiment to clarify whether vibration measurement values on the tool handle, in accordance with ISO 5349-1, can assess risk from workplace environments. The study investigated the relationship between the vibration magnitude of a hand-held electric drill with different operating postures. The experiment included the determination of the participant’s temporary threshold shift (TTS) of vibrotactile perception threshold (VPT) at the tip of the index finger. The experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 14 publications
0
10
1
Order By: Relevance
“…The effect of arm posture on the total acceleration measured at the tool handle is consistent with previously reported results where certain operating postures were reported to increase the vibration acceleration at the handle of the tool. 16 Some adopted hand-arm postures can increase the quasi-static stresses, strains, and deformations of the tissues leading to altering the vibration transmission through the hand-arm system and increasing the potential development of HAVS or other vibration-induced muscle injuries. 9 However, it has to be noted that other studies conducted with hand-held grinders did not find any significant differences in the frequency-weighted acceleration at different parts of the hand-arm system with different working postures which may imply that the effect of the hand-arm posture on the vibration transmitted to the hand-arm system is dependent on the operated power tool.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The effect of arm posture on the total acceleration measured at the tool handle is consistent with previously reported results where certain operating postures were reported to increase the vibration acceleration at the handle of the tool. 16 Some adopted hand-arm postures can increase the quasi-static stresses, strains, and deformations of the tissues leading to altering the vibration transmission through the hand-arm system and increasing the potential development of HAVS or other vibration-induced muscle injuries. 9 However, it has to be noted that other studies conducted with hand-held grinders did not find any significant differences in the frequency-weighted acceleration at different parts of the hand-arm system with different working postures which may imply that the effect of the hand-arm posture on the vibration transmitted to the hand-arm system is dependent on the operated power tool.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has investigated whether the effect of the posture of the operator of an electric drill is included in the vibration measured on the handle of the drill. 16 The results showed that the vibration measured on the tool handle could not predict the temporary threshold shift of vibrotactile perception threshold after the exposure to vibration with different postures and hence, the study concluded that measurement of vibration on the handle of the drill using ISO 5349-1 22 does not include the effect of the operator posture. This has an implication on the suitability of using the current standard for assessing the potential hazard from power tools at varying postures.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…To show the influence of posture during hand-arm vibration exposure, different approaches such as magnitude of the vibration and feed and gripping forces for different working directions are applied [10][11][12][13]. While significant lower vibration magnitude was measured for working horizontally compared to vertical directions [12], significant influence of the body posture on the acceleration of the main handle was shown by means of feed and gripping forces [13].…”
Section: Introductionmentioning
confidence: 99%